Cyclin D-CDK Subunit Arrangement Is Dependent on the Availability of Competing INK4 and p21 Class Inhibitors - Parry, David (American Society for Microbiology, 1999)
The D-type cyclins and their major kinase partners CDK4 and CDK6 regulate G(0)-G(1)-S progression by contributing to the phosphorylation and inactivation of the retinoblastoma gene product, pRB. Assembly of active cyclin D-CDK complexes in response to mitogenic signals is negatively regulated by INK4 family members. Here we show that although all four INK4 proteins associate with CDK4 and CDK6 in vitro, only p16(INK4a) can form stable, binary complexes with both CDK4 and CDK6 in proliferating cells. The other INK4 family members form stable complexes with CDK6 but associate only transiently with CDK4. Conversely, CDK4 stably associates with both p21(CIP1) and p27(KIP1) in cyclin-containing complexes, suggesting that CDK4 is in equilibrium between INK4 and p21(CIP1)- or p27(KIP1)-bound states. In agreement with this hypothesis, overexpression of p21(CIP1) in 293 cells, where CDK4 is bound to p16(INK4a), stimulates the formation of ternary cyclin D-CDK4-p21(CIP1) complexes. These data suggest that members of the p21 family of proteins promote the association of D-type cyclins with CDKs by counteracting the effects of INK4 molecules.